(untitled) (Physical Education, Health and Social Sciences, 2025)
Dizziness is an impression of turning or spinning. The patient feels or thinks motion as a result of the vestibular system’s dysfunction. It is associated with vertigo, nausea, and difficulty standing and walking. The most common cause of vertigo is BPPV, impacts between 20% and 40% of patients with peripheral vestibular disease affecting the PC. This study’s objective was to determine the comparative effects of SLM and CCE in PC BPPV. This is quasi experimental study in which we collected data from Allied Hospital and National hospital Faisalabad. Twenty-eight patients with BPPV participate among two groups. Group A got SLM and group B got CCE in this study. The intervention was performed three times per week for 3 weeks. Liberatory maneuver depends on the theory of cupulolisthiasis. It includes quickly guiding the sufferer through resistance intended to remove the debris from cupula. CCE was utilized to energize and rush the rebuilding of equilibrium to diminish episodes of lightheadedness. Patients were made to lie in prostrate if patient can’t sit up. In any case, the patients were made to sit in any situation without arm rest. The patients were included on the basis of criteria for inclusion and exclusion. SPSS version 20 was utilized for the analysis of the data.